2022
DOI: 10.1002/adom.202200038
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman Scattering of In‐Plane Anisotropic Phonon Modes in α‑MoO3

Abstract: The recent discovery of in‐plane hyperbolic phonon polaritons in biaxial polar crystal—α‐MoO3, has aroused a huge research upsurge on anisotropic photonic quasiparticles in van der Waals materials. The physical origin of these highly anisotropic phonon polaritons is attributed to the strong anisotropy of crystal phonons. However, the orientation‐dependent phonon modes have not been fully understood from crystallographic point of view. This work systematically performs in situ angle‐resolved polarized Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
(57 reference statements)
4
13
0
Order By: Relevance
“…In the parallel polarization configuration (Figure 3b), we observed four anomalous ARPRS responses of A g modes on bulk-like α-MoO 3 as shown in Figure 3c-e and Figure S2, Supporting Information. Specifically, in the responses of modes A g 3 (217.0 cm −1 ), A g 4 (337.5 cm −1 ), A g 6 (818.2 cm −1 ), and A g 7 (994.2 cm −1 , with a response similar to that of A g 4 ), there is a secondary maximum (which of A g 4 and A g 7 are too large to show an isotropic-like response) that cannot be reproduced using the real Raman tensor commonly used in previous studies on α-MoO 3 [32,33,35,38] as shown by the blue lines in Figure 3c-e. However, using the birefringence-induced Raman selection rule shown below, the ARPRS responses of A g modes can be well-fitted, as shown by the red lines.…”
Section: Birefringence-induced Raman Selection Rulesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the parallel polarization configuration (Figure 3b), we observed four anomalous ARPRS responses of A g modes on bulk-like α-MoO 3 as shown in Figure 3c-e and Figure S2, Supporting Information. Specifically, in the responses of modes A g 3 (217.0 cm −1 ), A g 4 (337.5 cm −1 ), A g 6 (818.2 cm −1 ), and A g 7 (994.2 cm −1 , with a response similar to that of A g 4 ), there is a secondary maximum (which of A g 4 and A g 7 are too large to show an isotropic-like response) that cannot be reproduced using the real Raman tensor commonly used in previous studies on α-MoO 3 [32,33,35,38] as shown by the blue lines in Figure 3c-e. However, using the birefringence-induced Raman selection rule shown below, the ARPRS responses of A g modes can be well-fitted, as shown by the red lines.…”
Section: Birefringence-induced Raman Selection Rulesmentioning
confidence: 93%
“…Previous polarized Raman studies on α-MoO 3 have tended to focus on selected Raman modes or sample thicknesses. [32][33][34][35] Several additional physical questions remain unanswered such as the exploration and reproduction of anomalous ARPRS responses in α-MoO 3 with rich Raman fingerprints that cannot be fitted with real Raman tensors widely used for non-absorbent Optical anisotropy, which is quantified by birefringence (Δn) and linear dichroism (Δk), can significantly modulate the angle-resolved polarized Raman spectroscopy (ARPRS) response of anisotropic layered materials (ALMs) by external interference. This work studies the separate modulation of birefringence on the ARPRS response and the intrinsic response by selecting transparent birefringent crystal α-MoO 3 as an excellent platform.…”
mentioning
confidence: 99%
“…where 8A g , 8B 1g , 4B 2g , 4B 3g are Raman active, and others are infrared-active modes. [42,43] Peaks at 992 and 814 cm À1 correspond to symmetric stretching of Mo═O and Mo─O─Mo in MoO 3 , [32] whereas the peaks between 1600 and 1300 cm À1 correspond to the stretching vibrations of the imidazole ring and 800-990 cm À1 corresponds to Mo-O stretching and bending vibrations in case of Mo-MOF. [44,45] SEM analysis is also a valuable method for studying the samples' shape, size, and microstructure information.…”
Section: Resultsmentioning
confidence: 99%
“…[58] Recently, α-MoO 3 has attracted numerous research interests on anisotropic photonic quasi-particles in vdW materials due to the discovery of in-plane hyperbolic phonon polaritons in such a biaxial polar crystal. [59][60][61][62] The twisting stacked α-MoO 3 slabs have achieved a configurable light-matter waves-phonon polaritons over a broad range of twist angles, giving the potential for tunable nanophotonic devices. [61,62] Figure 3c exhibits the electrical conductivity anisotropy of α-V 2 O 5 .…”
Section: Defects In 2d Metal Oxidementioning
confidence: 99%